Meningkatkan Hasil Belajar Pendidikan Agama Islam Menggunakan Metode Tanya Jawab Kelas VIII SMP Negeri 1 Akabiluru - Zainal Fitriadi; Salmiwati Salmiwati; Rina Mala Putri (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) in class VIII students of SMP Negeri 1 Akabiluru through the application of question-and-answer method. The question-and-answer method was chosen because it is able to actively involve students in the learning process and provide opportunities for them to develop a deeper understanding of the material being studied. This research is classroom action research (PTK) conducted in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were students of class VIII SMP Negeri 1 Akabiluru with a total of 32 students. The data collected included student learning test results, student activity observation sheets, and field notes. The results showed a significant increase in student learning outcomes after the application of the question-and-answer method. In cycle I, the average student score reached 72, with a completeness percentage of 68.75%, while in cycle II the average student score increased to 85, with a completeness percentage of 90.62%. From the results of this study, it can be concluded that the question-and-answer method is effective in improving the learning outcomes of Islamic Religious Education of 8th grade students of SMP Negeri 1 Akabiluru. This method not only increases students' understanding of the material, but also encourages active participation and student involvement in the learning process.